Data dissemination by Uganda Bureau of Statistics - Judith Nyangoma (IASSIST Quarterly, 2021)
Data plays a big role in educating the population on various issues that contribute to development. One of the major activities conducted after data collection is, dissemination of the data to different stakeholders. Uganda Bureau of Statistics disseminates data to its users through a number of channels. This paper discusses each method in detail and how it's used during this process. The major channel of sharing data with users is through dissemination workshops and the website. Other channels used for dissemination include the library and resource centre, social media and physical delivery to stakeholders in district public libraries. Having the above-mentioned channels of data dissemination in place, has helped UBOS remain the centre of excellence in dissemination of data to users, countrywide and in Africa.